The Good, the Bad and the Right: Formal Reductions among Deontic Concepts - Glavaničová, Daniela; Pascucci, Matteo (Bulletin of the Section of Logic, 2021)
The present article provides a taxonomic analysis of bimodal logics of normative ideality and normative awfulness, two notions whose meaning is here explained in terms of the moral values pursued by a given community. Furthermore, the article addresses the traditional problem of a reduction among deontic concepts: we explore the possibility of defining other relevant normative notions, such as obligation, explicit permission and Hohfeldian relations, in terms of ideality and awfulness. Some proposals in this respect, which have been formulated in the literature over the years, are here improved and discussed with reference to the various logics that we will introduce.